Implementing of Think-Pair-Share In Teaching Speaking Ability to The Seventh Grade Students of SMP Negeri 9 Parepare - Abd. Wahid (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2020)
This research was based on the students’ problem regarding the English teaching, especially in speaking in the classroom. Which is the teacher was more active rather than students in learning process. Therefore, the objective of this research is to find out whether or not the speaking ability improves to the seventh-grade students of SMP Negeri 9 Parepare before and after given taught by implementing think-pair-shar as strategy. This researcher applied quasi-experimental design, with two group pre-test and post-test design. The population of this research was seventh grade students of SMP Negeri 9 Parepare. Total number of population was 112 students and was taken as sample by using cluster random sampling technique, class VII.1 as experimental class and class VII.4 as control class. the number of each class was 63 students. The material in this research were about descriptive text to know the student’s ability in the application of think-pair-share as strategy in teaching speaking. The researcher reveals that there is significant difference between experimental class and control class, that indicated from the mean score of the experimental class is 53,56 in pre-test to 70,90 in post-test, while that of the control class is 46,19 in pre-test to 61,25 in post-test. It is concluded that speaking ability can improve by implemented of think-pair-share.